THE VIOLATION OF GRICE’S MAXIM IN “BAD GENIUS” MOVIE - Dinda Ayuna Putri; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2020)
This study was focused on the violation based on Grice Maxim’s Cooperative Principle theory in the communication of characters in Bad Genius Movie. The purpose of this study is to analyze the violation of a sentence for every dialogue that is brought up by the main actor and the other person in the movie. The type of this research is descriptive qualitative and descriptive analysis method is used in analyzing the data. The data was collected from the conversation in the movie which contains conversational implicature in the character’s utterances. The authors analyzed how the dialogue refers to the violation maxim contained in the film "Bad Genius". The results of identification showed that are violations maxim Quantity, Quality, Relations, and Manner.Keywords:      Maxims, Violation, Bad Genius Movie